Market Proxies at BSE and Weak Form Efficiency - Sharma, Renuka; Chander, Ramesh (Indian Journal of Finance, 2011)
The Indian stock market has faced many challenges in last decade. The efficiency of stock markets on all terms; operational efficiency, allocation efficiency and pricing efficiency; has increased during the financial sector reforms regime. The present study is confined to pricing efficiency, where the investors can earn purely risk-adjusted return from their investment and the stock prices are assumed to be moving in an unbiased manner. The notion "efficiency" has been defined by many experts in different ways. The development of the theory of EMH took place in 1900, when Bachelier introduced the theoretical framework of EMH and he first modeled the random walk in security prices. Although his work did not get much attention, it took around 50 years to get his work rediscovered by various financial experts.